The EFFORT OF SECURITY INTELLIGENCE UNIT THROUGH INTELLIGENCE RAISING TO AVOID THE CRIMINAL CASE OF THEFT AGGRAVATING CIRCUMTANCES ON WORKERS COMMUNITY IN TEGAL DISTRICT POLICE JURISDICTION: UPAYA UNIT INTELKAM MELALUI PENGGALANGAN GUNA MENCEGAH PENCURIAN DENGAN PEMBERATAN PADA KOMUNITAS PEKERJA DI WILAYAH HUKUM POLRES KABUPATEN TEGAL - Raharstya Nursyawardhani Prabu (Police Studies Review, 2022)
The criminal case of theft aggravating circumtances that occurs in the jurisdiction of tegal regency police becomes the background in writing this final task. Based on the data that the author get, that from 2018 to 2020 The criminal case of theft aggravating circumtances have always been the most prevalent. This research discusses the efforts of The Intelligence Security Unit through intelligence raising to prevent The criminal case of theft aggravating circumtances in the jurisdiction of tegal regency police. This research uses data collection techniques with interviews, observations, and document studies and this research uses a qualitative approach. The theory the author uses is P.O.A.C management theory and the concepts used are the concepts of effort, intelligence raising, community workers, and The criminal case of theft aggravating circumtances. After the author conducted the research, it was found that the intelligence raising activities by the Tegal Regency Police Intelligence Security Unit became set aside due to several factors, one of which was that members of the Tegal Regency Police including members of the Intelligence Security Unit were involved in health protocol control activities amid the Covid-19 pandemic and the implementation of vaccinations. The findings of the next author are that the perpetrators of theft with many blessings come from outside Tegal Regency such as Cirebon and Brebes. The advice given to the Intelligence Security Unit is that although health protocol and vaccination activities are involved, intelligence raising can also be included in the middle of the implementation of these activities. By carrying out management that can adjust to the existing situation and conditions, the implementation can still be carried out and even more carried out from the annual yearly planning and the network formed is also increasingly widespread due to the use of health protocol and vaccination control activities that are widespread throughout the Tegal Regency area.